Exploring Suicidal Ideation Among High School Students in Central Java: A Comprehensive Analysis - Norma Nida Jayanti; Fayruziyah Ifroch Sabtana; Yuli Nurmalasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
There has been an increase in suicides in Indonesia in recent years. Suicide is the leading cause of death in the 15-29 age group. Suicide attempts begin with suicidal ideation. Suicidal ideation arises because the pain or suffering experienced by individuals occurs continuously. This study aims to analyze suicidal ideation that arises due to hopelessness and the desire to be free from pain in adolescents. Data were collected using a questionnaire adapted from the Columbia-Suicide Severity Rating Scale (C-SSRS). The study was conducted on 1154 students at one of the high schools in Central Java. The results showed that 12% of students had the idea to make a suicide attempt. Further results showed that 86% of respondents did not have a specific plan to commit suicide, 58% of respondents thought about suicide less than once a week, 41% of respondents were able to control suicidal ideation easily, 40% of respondents thought family, religion, and the pain of death could stop suicidal thoughts, and 35% of respondents made suicidal ideation as an attempt to end pain. This shows that suicidal ideation in adolescents is a problem that needs attention from various parties, one of which is the Guidance and Counseling teacher.